Master plan, St. Theresa Parish, Palm Springs, Calif. - William F. Cody::::::::: (1966)
Site is situated between Ramon Rd., Compadre Rd., and Vaquero Rd., and includes a multi-purpose gymnasium; church building with sanctuary, chapels, shrines, baptistry and other features; a rectory; an athletic field; a convent; and a school campus. The plan calls for a school that can accommodate 800 students, a church building with 900 seats, and parking lots that can hold 302 cars.